2020
DOI: 10.1016/j.jcmgh.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatic Bile Acid Uptake by Myrcludex B Promotes Glucagon-Like Peptide-1 Release and Reduces Obesity

Abstract: Background & Aims Bile acids are important metabolic signaling molecules. Bile acid receptor activation promotes body weight loss and improves glycemic control. The incretin hormone GLP-1 and thyroid hormone activation of T4 to T3 have been suggested as important contributors. Here, we identify the hepatic bile acid uptake transporter Na + taurocholate co-transporting polypeptide (NTCP) as target to prolong postprandial bile acid signaling. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…It has been shown to be safe and well-tolerated 17,18 and is currently in phase 2b and phase 3 clinical trials for treatment of HBV and HDV infections, respectively. Because myrcludex B inhibits hepatic bile uptake, it might be potentially used to treat metabolic diseases, which is supported by the current study of Donkers et al 13 These novel data demonstrate that NTCP inhibition decreases hepatic bile acid clearance and induces glucagon-like peptide 1 (GLP-1) mediated thermogenesis in brown adipose tissue, stimulates fatty acid oxidation, and increases fecal energy excretion, leading to a reduction in body weight and hepatic steatosis. At the same time, thyroid hormone activation and energy expenditure were not affected by myrcludex B.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…It has been shown to be safe and well-tolerated 17,18 and is currently in phase 2b and phase 3 clinical trials for treatment of HBV and HDV infections, respectively. Because myrcludex B inhibits hepatic bile uptake, it might be potentially used to treat metabolic diseases, which is supported by the current study of Donkers et al 13 These novel data demonstrate that NTCP inhibition decreases hepatic bile acid clearance and induces glucagon-like peptide 1 (GLP-1) mediated thermogenesis in brown adipose tissue, stimulates fatty acid oxidation, and increases fecal energy excretion, leading to a reduction in body weight and hepatic steatosis. At the same time, thyroid hormone activation and energy expenditure were not affected by myrcludex B.…”
mentioning
confidence: 56%
“…At the same time, thyroid hormone activation and energy expenditure were not affected by myrcludex B. 13 GLP-1 analogues themselves have been already identified as potential targets to treat obesity and NAFLD because they decrease body weight and improve histologic features of NAFLD and NASH 19 and also reduce the risk of cardiovascular diseases. 20 However, NTCP inhibition might be superior to GLP-1 agonists by using and prolonging the natural meal-dependent bile acid dynamics.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies in mice offer promise for additional applications of NTCP inhibitors in conditions of hypercholesterolemia, obesity and cholestasis. (50)(51)(52) NtCp-DeFICIeNt MICe NTCP-deficient mice, first described by Slijepcevic et al, (53) showed that some redundancy exists in hepatocytic uptake systems for bile salts in mice, due to the expression of other transporters of the organic anion transporting polypeptide (OATP) 1a/1b family. Most mice displayed no elevated bile salt levels at all, whereas a subset of these KO mice exhibited strong hypercholanemia.…”
Section: Ntcpmentioning
confidence: 99%